A Numerical Model of Mechanical Interaction between Rough Surfaces of Tribosystem of the High Forced Diesel Engine. (2015) - Goritskiy, Y.; Gavrilov, K.V.; Rozhdestvenskii, Y.V.; Doikin, A.A.
Abstract: The paper analyzes the numerical model of interaction between the rough surfaces of a piston-cylinder liner tribosystem in the form of a Markov chain. It is based on a model that takes into account elastic and plastic deformation and fatigue failure under load. We have provided a system of equations for the distribution of time-varying heights of protrusions. We have also analyzed the evolution of distributions for the contact interface of the piston-cylinder liner tribosystem of the diesel engine.